PID Testing Method Suitable for Process Control of Solar Cells Mass Production - Xianfang Gou; Xiaoyan Li; Su Zhou; Shaoliang Wang; Weitao Fan; Qingsong Huang (International Journal of Photoenergy)
Voltage bias of several hundred volts which are applied between solar cells and module frames may lead to significant power losses, so-called potential-induced degradation (PID), in normal photovoltaic (PV) installations system. Modules and minimodules are used to conduct PID test of solar cells. The test procedure is time consuming and of high cost, which cannot be used as process monitoring method during solar cells fabrication. In this paper, three kinds of test including minimodule, Rsh, and V-Q test are conducted on solar cells or wafers with SiNx of different refractive index. All comparisons between test results of Rsh, V-Q, and minimodule tests have shown equal results. It is shown that Rsh test can be used as quality inspection of solar cells and V-Q test of coated wafer can be used as process control of solar cells.